Undifferentiated human adipose-derived stromal/stem cells loaded onto wet-spun starch-polycaprolactone scaffolds enhance bone regeneration : nude mice calvarial defect in vivo study - Carvalho, P. P. (2014)
The repair of large bony defects remains challenging in the clinical setting. Human adipose-derived stromal/ stem cells (hASCs) have been reported to differentiate along different cell lineages, including the osteogenic. The objective of the present study was to assess the bone regeneration potential of undifferentiated hASCs loaded in starchpolycaprolactone (SPCL) scaffolds, in a critical-sized nude mice calvarial defect. Human ASCs were isolated from lipoaspirate of five female donors, cryopreserved, and pooled together. Critical-sized (4 mm) calvarial defects were created in the parietal bone of adult male nude mice. Defects were either left empty, treated with an SPCL scaffold alone, or SPCL scaffold with human ASCs. Histological analysis and Micro-CT imaging of the retrieved implants were performed. Improved new bone deposition and osseointegration was observed in SPCL loaded with hASC engrafted calvarial defects as compared to control groups that showed little healing. Nondifferentiated human ASCs enhance ossification of nonhealing nude mice calvarial defects, and wet-spun SPCL confirmed its suitability for bone tissue engineering. This study supports the potential translation for ASC use in the treatment of human skeletal defects.